Specificities of agriculture, innovation and development in the Mediterranean region - Di Mambro A. (Innovation in the Mediterranean agrifood sector. Concepts, experiences and actors in a developing ecosystem, 2016)
Mediterranean agriculture and food production now have to face the great challenges of ensuring sufficient healthy and nutritious food to feed the population. Overcoming these challenges requires a great effort to transfer knowledge and accelerate innovation. The Mediterranean is a kind of microcosm representing many of the current challenges to agrifood production and consumption models. Some of these are particularly urgent: declining biodiversity, climate change, the shift towards new and not always sustainable food consumption habits, dependence on supplies, are all unknown factors that may be revealed and managed only with a strong input of technological and organisational innovation. Although the specificities of agriculture mean that models imported from other sectors cannot function, it would be a mistake to refuse the opportunity of networking with players outside the traditional innovation ecosystem. Farming involves dealing with many unprecedented risks because, in addition to the traditional risk posed by the climate, there are now also political and market variables. The agricultural innovation ecosystem should begin to reorganise itself from within, seizing the opportunity offered by a phase of transition towards open innovation models.